Bcl-xL Is Required by Primary Hippocampal Neurons for Mitochondrial Motility and Proper Neurite Development. (14th June 2022) - Jansen, Joseph; Scott, Madison; Amjad, Emma; Stumpf, Allison; Lackey, Kimberly; Caldwell, Kim; Park, Han-A
Abstract: Objectives: Neurite branching is necessary to achieve neurite complexity and synaptic plasticity. Therefore, understanding how neurons utilize intracellular energy to support neurite branching is key to elucidating cellular mechanisms of neuronal development. B-cell lymphoma extra large (Bcl-xL) is a pro-survival protein found in the mitochondria. Traditionally, Bcl-xL is known to block apoptotic pathway, yet increasing studies have demonstrated that Bcl-xL exhibits additional biological roles. Bcl-xL has been reported to enhance neuronal energy metabolism and synapse formation, and we have previously shown Bcl-xL to be essential for neurite outgrowth and Bcl-xL depletion increases susceptibility to hypoxia. In this study, we hypothesized that Bcl-xL supports neurite branching and maintains neurite ATP via regulation of mitochondrial motility. Methods: Primary hippocampal neurons were transduced with either Bcl-xL shRNA or scrambled shRNA for 3 weeks. Mitochondria were labeled using mito-RFP BacMam2.0 and fluorescent and micrograph sequences were obtained. Mitochondrial motility parameters were then quantified using the KymoAnalyzer software. The ATP/ADP ratio was analyzed using the PercevalHR fluorescence biosensor to determine the effects of Bcl-xL depletion on energy retention. Neurite branching was quantified using Sholl analysis. Immunocytochemistry was performed to measure synapse formation. To measure susceptibility to excitotoxicity Fluorescent imaging using Fluo-4, propidium iodine, and calcein-AM was performed. Results: We found that Bcl-xL depletion decreases antero- and retrograde movement of mitochondria. Bcl-xL depletion also lowered the ATP/ADP ratio in neurites and decreased the length and branching of neurites. Furthermore, Bcl-xL depletion impaired synapse formation and increased susceptibility to excitotoxicity. Conclusions: This data suggests that Bcl-xL is essential in supporting neurite branching and energy retention by regulating mitochondrial motility. Bcl-xL may be a potential therapeutic target for brain disorders associated with abnormal or absent neurite development. Funding Sources: Sigma Xi Grants in Aid of Research (The National Academy of Sciences).